New Developments in Greco-Roman Archeology in Palestine - Strange, James F. (The Biblical archaeologist, 1982)
Greco-Roman archeology in ancient Palestine is developing in new quantitative directions that stress new methods of analyzing the data. Some surprising inferences are possible that go far beyond the old descriptions and measurements.